On marginal Markov processes of quantum quadratic stochastic prosses - Mukhamedov, Farrukh (World Scientific, 2010)
In this paper quantum quadratic stochastic process (q.q.s.p.) on von Meumann algebra M is considered. It is de¯ned two marginal Markov processes on von Neumann algebras M and MM, respectively, to given q.q.s.o. We prove that such marginal processes uniquely determine the q.q.s.p. Moreover, certain ergodic relations between marginal processes and q.q.s.p. are established.